2007
DOI: 10.1080/13550280601178226
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling reveals that rabies virus infection results in differential expression of host proteins involved in ion homeostasis and synaptic physiology in the central nervous system

Abstract: To understand how rabies virus (RV) infection results in neuronal dysfunction, the authors employed proteomics technology to profile host responses to RV infection. In mice infected with wild-type (wt) RV, the expression of proteins involved in ion homeostasis was altered. H(+) ATPase and Na(+)/K(+) ATPase were up-regulated whereas Ca(2+) ATPase was down-regulated, which resulted in reduction of the intracellular Na(+) and Ca(2+) concentrations. Furthermore, infection with wt RV resulted in down-regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 55 publications
2
48
0
Order By: Relevance
“…No evidence of apoptosis has been observed in postmortem brain tissues from fatal human rabies cases . Proteomic analysis indicated that only attenuated strains stimulate the expression of proapoptotic proteins; proteins that play a critical role in inducing apoptosis (Dhingra et al, 2007). It is believed that the expression level of viral glycoprotein is a critical factor for inducing apoptosis as attenuated strains produce a greater amount of glycoprotein in comparison with pathogenic strains (Faber et al, 2002 andPrehaud et al, 2003).…”
Section: Host Immune Responsementioning
confidence: 99%
“…No evidence of apoptosis has been observed in postmortem brain tissues from fatal human rabies cases . Proteomic analysis indicated that only attenuated strains stimulate the expression of proapoptotic proteins; proteins that play a critical role in inducing apoptosis (Dhingra et al, 2007). It is believed that the expression level of viral glycoprotein is a critical factor for inducing apoptosis as attenuated strains produce a greater amount of glycoprotein in comparison with pathogenic strains (Faber et al, 2002 andPrehaud et al, 2003).…”
Section: Host Immune Responsementioning
confidence: 99%
“…In contrast, only about 1.4% of genes became upregulated, including genes involved in regulation of cell metabolism, protein synthesis, and growth and differentiation. Using proteomic profiling on brain homogenates in mice infected with the street rabies virus, Dhingra et al 36 found that the expression of proteins involved in ion homeostasis was altered (H + ATPase and Na + /K + ATPase were upregulated and Ca 2+ ATPase were downregulated), and there was downregulation of proteins relevant to synaptic physiology, which are involved in docking and fusion of synaptic vesicles to the presynaptic membrane. These abnormalities could all a play a role in neuronal dysfunction.…”
Section: Mechanisms For Neuronal Dysfunction and Deathmentioning
confidence: 99%
“…Using iTRAQ quantitative proteomic method, Venugopal et al detected overexpression of functionally diverse proteins including karyopherin alpha 4 (KPNA4), calcium calmodulin-dependent kinase 2 alpha (CAMK2A), and glutamate ammonia ligase (GLUL) in postmortem rabies brains [69]. Likewise, protein profiling of mouse brains infected with rabies has shown differential expression of proteins involved in ion homeostasis and synaptic function [70].…”
Section: Proteomics Studies On Viral Infections Of the Nervous Systemmentioning
confidence: 98%